Migratory encounters, common idiom, and the king: The relationship between two Roma groups from Poland in transnational social space - ELŻBIETA MIRGA-WÓJTOWICZ; MICHAŁ P. GARAPICH; KAMILA FIAŁKOWSKA (Romani Studies)
Roma ethnicity presents scholars with plenty of conceptual and methodological challenges, which in the light of the increased mobility of that largest European minority after EU enlargements has additionally perplexed academics and policymakers alike. This article presents our fieldwork data derived from encounters and conversations with Roma individuals in Poland and England. Our approach to this issue is rooted in the emic perspective, examining how Roma people navigate and cope with their own heterogeneity. By focusing on the relationship between two Roma groups from Poland, namely Polska Roma and Bergitka (or Carpathian) Roma, we shed light on Roma’s practical approaches to their group identity. We explore what is at stake when boundaries are encountered, negotiated, and occasionally bridged, in particular when it comes to gender and conflict resolution strategies. In the article, we account for the two groups’ interconnections through the history of migrations and current modes of transnational living. We show how, interestingly, nationality or common country of origin may become the binding factor. This article was published open access under a CC BY licence: https://creativecommons.org/licences/by/4.0.